Profile of Daily Life in Children with Brain Tumors: An Assessment of PedsQL 4.0 Generic Core Scales before and after Treatment - July, Julius; Bastiaan, Natasha; Tandean, Steven; Loe, Michael Lumintang (Open Access Macedonian Journal of Medical Sciences, 2020)
BACKGROUND: Pediatric brain tumors are the most common solid tumor and cause of death among all childhood cancers. In America, brain tumor prevalence is 21.42/100.000 population. Even though survival rate is improving, the impact of treatment for long-term quality of life is still a challenge. AIM: We aimed to investigate quality of life score using PedsQL 4.0 Generic Core Scales. METHODS: The data collected based on the inclusion criteria from patient’s medical records 2015–2017 period on January 2018–May 2018 in Siloam Hospital, Lippo Village, Karawaci. Twenty-six brain tumor pediatric patients with surgical treatment were evaluated using PedsQL 4.0 Generic Core Scales. The evaluation included before and after condition of the patient. PedsQL 4.0 Generic Core Scales were divided into four categories; physical function, emotional function, social function, and school function. They were analyzed statically using Wilcoxon test with p < 0.05 considered as statistically significant. RESULTS: The result showed that before treatment score of PedsQL 4.0 Generic Core Scales was classified as medium functioning (58.54/92) and after treatment score of PedsQL 4.0 Generic Core Scales was classified as intermediate functioning (37.3/92). CONCLUSION: The conclusion is that patient after treatment (surgery, chemotherapy, and radiation) shows improved quality of life score using PedsQL 4.0 Generic Core Scales.